Greenland, view of Kjerulf Fjord through to Dicksons Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background: Right Valley. Glacier descends north side towards western end. Range faces south and here is shown reaching its N.E. terminal --where it turns north to form the west side of Main Valley. In foreground Left Valley, with its descending stream (sourced by waters off Hisinger Glacier [Hisinger Gletscher]). Photo taken looking W.N.W. See sequence: 27-1-10; 9-8-7.